E-cadherin Expression in Canine Gastric Carcinomas: Association with Clinicopathological Parameters - Ana R. Flores; Alexandra Rêma; João R. Mesquita; Marian Taulescu; Fernanda Seixas; Fátima Gärtner; Irina Amorim (Veterinary Sciences, 2022)
E-cadherin (E-cad) is a cell-adhesion molecule known for its tumor-invasion suppressor function. E-cad expression was examined immunohistochemically in a series of canine tissue samples, including normal gastric mucosa (NGM; n = 3), gastric carcinomas (GC; n = 33), adjacent non-neoplastic mucosa (NNM; n = 32), neoplastic emboli (n = 16) and metastatic lesions (n = 9). The relationship between E-cad expression and clinicopathological features were investigated. In NGM, epithelial cells showed strong latero-lateral membranous expression of E-cad, and this pattern was considered normal. The membranous staining was preserved in all specimens of NNM (100%), whereas abnormal E-cad expression was found in 87.9% of the GCs. A marked difference in E-cad expression was observed between normal and malignant tissues (p < 0.0002). Abnormal E-cad expression was significantly more frequent in poorly/undifferentiated carcinomas (96%) and diffuse (95%) and indeterminate carcinomas (100%) than in well-differentiated/intestinal ones (62.5%; p = 0.0115 and p = 0.0392, respectively). There was significant association between abnormal E-cad expression and the depth of invasion (p = 0.0117), and the presence neoplastic emboli (p = 0.0194). No statistically significant differences in E-cad expression were observed concerning tumor location, histological type according to WHO classification, and presence of metastatic lesions. Therefore, deregulation of E-cad expression may play a role in canine gastric carcinogenesis and in tumor progression; moreover, it might be a prognostic tool for canine gastric cancer.